2017
DOI: 10.1038/s41598-017-06106-1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of mutant allele frequency level of circulating cell-free DNA and blood cells in healthy individuals

Abstract: Cell-free DNA (cfDNA) in plasma has emerged as a potential important biomarker in clinical diagnostics, particularly in cancer. However, somatic mutations are also commonly found in healthy individuals, which interfere with the effectiveness for cancer diagnostics. This study examined the background somatic mutations in white blood cells (WBC) and cfDNA in healthy controls based on sequencing data from 821 non-cancer individuals and several cancer samples with the aim of understanding the patterns of mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…29 The mutant allele frequencies in cfDNA from apoptotic cells were almost identical with those in the blood cells. 29,30 Consistent with this, we observed that mutant allele frequencies in cfDNA were distinct from gDNA, and that had a significant correlation with gDNA in coexisting mutations. Therefore, a significant fraction of alterations identified in cfDNA should be considered as the background mutations from apoptotic DNA fragments.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…29 The mutant allele frequencies in cfDNA from apoptotic cells were almost identical with those in the blood cells. 29,30 Consistent with this, we observed that mutant allele frequencies in cfDNA were distinct from gDNA, and that had a significant correlation with gDNA in coexisting mutations. Therefore, a significant fraction of alterations identified in cfDNA should be considered as the background mutations from apoptotic DNA fragments.…”
Section: Discussionsupporting
confidence: 83%
“…Fragments of circulating cfDNA were shown to be derived from apoptosis, necrosis or active secretion, which can be detected in the cell‐free components of plasma and serum . The mutant allele frequencies in cfDNA from apoptotic cells were almost identical with those in the blood cells . Consistent with this, we observed that mutant allele frequencies in cfDNA were distinct from gDNA, and that had a significant correlation with gDNA in coexisting mutations.…”
Section: Discussionsupporting
confidence: 80%
“…The above collected DNA samples were analyzed by our proprietary Sec-Seq technique as described previously (17). Briefly, blood sample were processed to separate the plasma from blood cells by centrifugation.…”
Section: Sequencing Analysismentioning
confidence: 99%
“…In order to focus on the above questions, our previous studies explored new resin to increase the recovery rate in ctDNA extraction and examined the background somatic mutations originated from blood cells and cfDNA in 821 non-cancer individuals based on ultra-deep sequencing and we also described the baseline reference 18 . Now we are focusing on the understanding of ctDNA profiles in cancer patients after we developed an updated method called "Sec-Seq" with exogenous molecular barcoding and custom-probe capture to suppress the systematic errors and detect the genetic alterations including mutations, insertion and deletion in early stages of lung cancer.…”
Section: Introductionmentioning
confidence: 99%